2023
DOI: 10.3390/foods12040772
|View full text |Cite
|
Sign up to set email alerts
|

Surface Hygiene Evaluation Method in Food Trucks as an Important Factor in the Assessment of Microbiological Risks in Mobile Gastronomy

Abstract: Street food outlets are characterised by poor microbiological quality of the food and poor hygiene practices that pose a risk to consumer health. The aim of the study was to evaluate the hygiene of surfaces in food trucks (FT) using the reference method together with alternatives such as PetrifilmTM and the bioluminescence method. TVC, S. aureus, Enterobacteriaceae, E. coli, L. monocytogenes, and Salmonella spp. were assessed. The material for the study consisted of swabs and prints taken from five surfaces (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 74 publications
0
0
0
Order By: Relevance
“…This method detected that all the surfaces were unsatisfactory in terms of cleanliness; nevertheless, the bioluminescence assay can be highly variable in determining bacteria present on surfaces due to the presence of organic material that cannot be distinguished from the different types of microorganisms. Values obtained in this study are similar to those reported by Wiatrowski et al (2023), on five different surfaces on a mobile gastronomy truck (shelf of a refrigerator, cutting board, small utensil such as a knife, serving surface, and worktop surface). Additionally, the amount of ATP that a cell contains depends on its size and vital state so this can underestimate the number of cells viable but not cultivable (Ríos-Castillo et al, 2021).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…This method detected that all the surfaces were unsatisfactory in terms of cleanliness; nevertheless, the bioluminescence assay can be highly variable in determining bacteria present on surfaces due to the presence of organic material that cannot be distinguished from the different types of microorganisms. Values obtained in this study are similar to those reported by Wiatrowski et al (2023), on five different surfaces on a mobile gastronomy truck (shelf of a refrigerator, cutting board, small utensil such as a knife, serving surface, and worktop surface). Additionally, the amount of ATP that a cell contains depends on its size and vital state so this can underestimate the number of cells viable but not cultivable (Ríos-Castillo et al, 2021).…”
Section: Resultssupporting
confidence: 89%
“…were detected. These bacteria are indicators of a dirty environment, unhygienic production procedures, and poor water quality (Wiatrowski et al, 2023). Work areas, cutting boards, sinks, and kitchen faucets are recognized as important surfaces in food service facilities that might result in cross-contamination of food, especially if these surfaces are contaminated by mesophilic aerobic bacteria (Rodríguez et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations